An infinite sequence of real numbers a 1 , a 2 , … satisfies the recurrence a n + 3 = a n + 2 − 2 a n + 1 + a n for every positive integer n .
Given that a 1 = a 3 = 1 and a 9 8 = a 9 9 , compute a 1 + a 2 + ⋯ + a 1 0 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a n + 3 k = 1 ∑ n a k + 3 k = 4 ∑ n + 3 a k k = 1 ∑ n + 3 a k k = 1 ∑ 1 0 0 a k = a n + 2 − 2 a n + 1 + a n = k = 1 ∑ n ( a k + 2 − 2 a k + 1 + a k ) = a n + 2 − a n + 1 − a 2 + a 1 = a n + 2 − a n + 1 + a 3 + 2 a 1 = a 9 9 − a 9 8 + a 3 + 2 a 1 = a 3 + 2 a 1 = 1 + 2 = 3 Given Both sides add a 1 + a 2 + a 3 Putting n = 9 7 Since a 9 8 = a 9 9 Given that a 1 = a 3 = 1
list = LinearRecurrence [ { 1 , − 2 , 1 } , { 1 , x , 1 } , 1 0 0 ] ;
list [ [ 9 8 ;; 9 9 ] ] ⟹ { 4 3 7 7 6 3 2 8 2 6 3 5 − 5 9 5 8 6 6 6 2 2 3 2 9 x , 1 4 3 6 8 2 8 1 2 0 x − 3 0 4 9 8 2 3 1 9 3 1 9 } ⟹ x → 5 9 7 3 0 3 4 5 0 4 4 9 7 4 2 7 4 5 6 0 1 9 5 4
Plus @@ LinearRecurrence [ { 1 , − 2 , 1 } , { 1 , 5 9 7 3 0 3 4 5 0 4 4 9 7 4 2 7 4 5 6 0 1 9 5 4 , 1 } , 1 0 0 ] ⟶ 3
Problem Loading...
Note Loading...
Set Loading...
Let us denote sum of n terms is S ( n ) and n th term be denoted by a ( n ) .
a ( n + 3 ) = [ a ( n + 2 ) − a ( n + 1 ) − a ( n + 1 ) − a ( n ) ] . Let us name this equation as A .
Then by taking summation on both sides of equation A we have S ( n + 3 ) = a ( n + 2 ) − a ( n + 1 ) + a ( 1 ) − a ( 2 ) .
Let this equation be B . Now put n = 1 in A to get :
a ( 4 ) = a ( 3 ) − 2 a ( 2 ) + a ( 1 ) . Let this equation be C . Now put n = 1 in B . Then :
S ( 4 ) = a ( 1 ) − 2 a ( 2 ) + a ( 3 ) . Let this equation be D . Now eliminate a ( 4 ) from C and D to get a ( 2 ) = − 2 . Now put n = 9 7 in B to get S ( 1 0 0 ) = 1 − a ( 2 ) = 3 .